Epidemiology of cancers in Lahore, Pakistan, 2010–2012: a cross-sectional study. Issue 6 (28th June 2016) - Badar, Farhana; Mahmood, Shahid; Yusuf, Muhammed Aasim; Sultan, Faisal
Abstract : Objectives: To estimate the population-level cancer estimates for the Lahore district, which is part of the Punjab Cancer Registry (PCR), Pakistan. The average population per year of Lahore was estimated at 9.8 million in 2010–2012. Design: A cross-sectional study. Setting: The Registry has 19 collaborating centres in Lahore that report their data to the Central Office located within a tertiary care cancer treatment facility in Lahore, Pakistan. Participants: Patients belonging to Lahore, of any age-group, and diagnosed with cancer in 2010–2012, were included in the study. They were followed up between July and October 2015 to determine their vital status. Outcome measures: Summaries were generated for gender, the basis of diagnosis, diagnoses and deaths. The Age-Standardized Incidence Rates (ASIR) were computed per 100 000 population, by gender and cancer site. Five-year age categories were created from 0–4 until 70–74, followed by 75+ years. Death counts were reported by site. Results: Between 2010 and 2012, in Lahore, a total of 15 840 new cancers were diagnosed in 43% male patients and 57% female patients; 93.5% were microscopically confirmed and 6.5% non-microscopically. In females, the ASIR was 105.1 and in males, it was 66.7. ASIRs of leading cancers among women were breast 47.6, ovary 4.9 and corpus uteri 3.6, whereas among men they were prostate 6.4, bladder 5.0, and trachea, bronchus and lung 4.6. A total of 5134 deaths were recorded. Conclusions: In Lahore, the ASIR was higher in women than in men. Among women and men, breast cancer and prostate cancer, respectively, were the leading cancer types. These estimates can be used for health promotion and policymaking in the region.